Hypoglycaemia events with iGlarLixi versus premix biphasic insulin aspart 30 (BIAsp 30) in people with type 2 diabetes advancing from basal insulin: An analysis of the SoliMix trial. Issue 12 (23rd August 2022) - McCrimmon, Rory J.; Home, Philip; Cheng, Alice; Giorgino, Francesco; Fonseca, Vivian; Souhami, Elisabeth; Alvarez, Agustina; Picard, Pascaline; Rosenstock, Julio
Abstract: Aims: To explore details of the incidence and rates of daytime and nocturnal hypoglycaemia, levels of hypoglycaemia, and relationship to glycated haemoglobin (HbA1c), when comparing iGlarLixi versus premixed biphasic insulin aspart 30 (BIAsp 30) in the SoliMix randomized controlled trial. Materials and Methods: This exploratory analysis of SoliMix used logistic regression and negative binomial regression analyses to assess between‐treatment differences in the incidence and rates of hypoglycaemia by time of day. A negative binomial model was used to derive estimated annualized hypoglycaemia rates as a function of HbA1c. Results: iGlarLixi was associated with lower incidence and rates of American Diabetes Association Level 2 (<54 mg/dL [<3.0 mmol/L]) hypoglycaemia during both night and day versus BIAsp 30. Incidence and rates of Level 1 (<70 to ≥54 mg/dL [<3.9 to ≥3.0 mmol/L]) hypoglycaemia were also mostly shown to be reduced with iGlarLixi versus BIAsp 30. Severe (Level 3) events were too few for analysis (n = 3). iGlarLixi was associated with lower modelled event rates of Level 2 and Level 1 hypoglycaemia over a wide range of HbA1c levels versus BIAsp 30. Conclusions: These results show that the lower HbA1c levels and weight benefit seen with iGlarLixi versus premixed BIAsp 30 in people with type 2 diabetes advancing their basal insulin therapy in the SoliMix trial are also accompanied by a lower risk of hypoglycaemia at any time of day and across a broad range of HbA1c levels.